2011
DOI: 10.1016/j.ijid.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel influenza A (H1N1): clinical features of pediatric hospitalizations in two successive waves

Abstract: Children hospitalized during the two successive waves of H1N1 were mainly school-aged and suffered from moderate disease. Although clinical features and severity of disease were similar, oseltamivir was prescribed more frequently and the length of hospital stay was shorter in the second wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…3 6 7 9 10 Several smaller studies have described paediatric patients admitted to intensive care units by city (Denver, n=80) state (California, n=96), and country (Australia and New Zealand, n=83; Argentina, n=147). [3][4][5][6][7][8][9][10][11][12][13][14][15] However, these studies typically described demographic data and comorbidities and did not focus on clinical predictors of severity. [5][6][7][8] Intensive care unit cohorts from California and Denver were compared with pH1N1 hospital admissions to non-intensive care.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 6 7 9 10 Several smaller studies have described paediatric patients admitted to intensive care units by city (Denver, n=80) state (California, n=96), and country (Australia and New Zealand, n=83; Argentina, n=147). [3][4][5][6][7][8][9][10][11][12][13][14][15] However, these studies typically described demographic data and comorbidities and did not focus on clinical predictors of severity. [5][6][7][8] Intensive care unit cohorts from California and Denver were compared with pH1N1 hospital admissions to non-intensive care.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…1 Several studies from around the world have included children and adults admitted to hospital or intensive care units with pH1N1 infection. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, these data vary in format and emphasis, making direct comparison between studies difficult. Furthermore, data on severe outcomes (including death) and risk factors for severe outcomes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…These two diseases were confirmed to be statistically significant risk factors of hospital admission. Precedent studies also reported asthma and neurologic diseases as risk factors of hospital admission in pediatric patients5,12-15. According to studies, asthma was most found in 22~37% of inpatients as an underlying disease5,12-15.…”
Section: Discussionmentioning
confidence: 99%
“…Precedent studies also reported asthma and neurologic diseases as risk factors of hospital admission in pediatric patients5,12-15. According to studies, asthma was most found in 22~37% of inpatients as an underlying disease5,12-15. In particular, a Canadian study reported that asthma was more important risk factor of hospital admission compared with the case of seasonal influenza, and even mild asthma was a risk factor5.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of risk factors was significantly higher in H1N1/09-positive patients than in H1N1/09-negative patients and two thirds of our hospitalized H1N1/09-positive patients had a risk factor compared to only one third among outpatients. Similarly, in case series of hospitalized patients, risk factors-lung diseases being the most prevalent-were highly prevalent [12] and associated with a greater risk of severe disease [5], including that of being admitted to PICU [9]. In an outpatient setting, Mahut et al showed that ILI and severe exacerbation are significantly and strongly associated in the H1N1 influenza pandemic in asthmatic children [15].…”
Section: Discussionmentioning
confidence: 99%